2023
DOI: 10.3389/fnut.2023.1117460
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the intervention mechanisms of polydatin in hyperuricemia model rats by using UHPLC-Q-Exactive Orbitrap mass spectroscopy metabonomic approach

Abstract: IntroductionPolydatin is a biologically active compound found in mulberries, grapes, and Polygonum cuspidatum, and it has uric acid-lowering effects. However, its urate-lowering effects and the molecular mechanisms underlying its function require further study.MethodsIn this study, a hyperuricemic rat model was established to assess the effects of polydatin on uric acid levels. The body weight, serum biochemical indicators, and histopathological parameters of the rats were evaluated. A UHPLC-Q-Exactive Orbitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Metabolomics is an emerging discipline in the 20th century and is of great importance in elucidating the mechanisms of pharmacological effects of Chinese medicines ( Wu et al, 2019 ). Recent reports have found that polydatin can improve and treat HUA through amino acid metabolism, lipid metabolism and energy metabolism ( Ge et al, 2023 ). Ma et al found that PC could upregulate the expression of Adenosine 5′-monophosphate-activated protein kinase (AMPK) and its downstream molecule FOXO3α, and inhibit the bioactivity of Toll-likereceptor4 (TLR4), NOD-like receptor thermal protein domain associated protein 3 (NLRP3) and Monocyte Chemoattractant Protein-1 (MCP-1), key signaling molecules of the immune inflammatory network pathway to improve HUA-mediated immunoinflammatory metabolic kidney damage ( Liu et al, 2005 ; Ma et al, 2019 ).…”
Section: Uric Acid-lowering Effects Of Botanical Drugs Extracts Activ...mentioning
confidence: 99%
“…Metabolomics is an emerging discipline in the 20th century and is of great importance in elucidating the mechanisms of pharmacological effects of Chinese medicines ( Wu et al, 2019 ). Recent reports have found that polydatin can improve and treat HUA through amino acid metabolism, lipid metabolism and energy metabolism ( Ge et al, 2023 ). Ma et al found that PC could upregulate the expression of Adenosine 5′-monophosphate-activated protein kinase (AMPK) and its downstream molecule FOXO3α, and inhibit the bioactivity of Toll-likereceptor4 (TLR4), NOD-like receptor thermal protein domain associated protein 3 (NLRP3) and Monocyte Chemoattractant Protein-1 (MCP-1), key signaling molecules of the immune inflammatory network pathway to improve HUA-mediated immunoinflammatory metabolic kidney damage ( Liu et al, 2005 ; Ma et al, 2019 ).…”
Section: Uric Acid-lowering Effects Of Botanical Drugs Extracts Activ...mentioning
confidence: 99%